Lipid metabolon in non-oleaginous fungus Aspergillus niger - Izyanti Ibrahim; Shuwahida Shuib; Yap, Yin Xin; Aidil Abdul Hamid (Penerbit Universiti Kebangsaan Malaysia, 2025)
The lipogenic multienzyme complex or lipid metabolon consisting of malic enzyme (ME), fatty acid synthase (FAS), acetyl-CoA carboxylase (ACC) and ATP:citrate lyase (ACL) was observed during lipid biosynthesis of an oleaginous fungus Cunninghamella bainieri 2A1. It is believed that high production of fatty acid in oleaginous species is due to the association of lipogenic enzymes forming a metabolon during lipid accumulation phase. One of the significances of lipid metabolon is that it provides efficient and rapid channel of NADPH directly from ME to FAS when lipid accumulation occurs. This leads to the assumption of low lipid yield in non-oleaginous microorganisms is due to the absence of lipid metabolon in these microorganisms. Thus, the non-oleaginous filamentous fungi Aspergillus niger was studied to see the association of lipid metabolon and lipid biosynthesis. The cells of A. niger during both lipid accumulation and lipid cessation phase were used to prepare cell-free extracts using protoplasting technique. The crude proteins were then separated by Blue Native (BN)-PAGE, associated with liquid chromatography-tandem mass spectrometry (LC-MS/MS). No high molecular mass complex was detected, speculating that no lipogenic multienzyme complex was formed in non-oleaginous fungi hence very low or no storage lipid was accumulated in this fungus.